Perlindungan Hukum Bagi Konsumen Sebagai Pemenang Lelang Eksekusi Hak Tanggungan atas Penguasaan Obyek Lelang - Ade Muhammad Syamkirana Putra; Tri Lisiani Prihatinah (Universitas Muhammadiyah Purwokerto, 2022)
AbstractLegal protection for the auction buyer/auction winner means that there is legal certainty of the auction winner's rights to the goods he bought through the auction, obtaining the goods and material rights to the goods he purchased or in other words the auction winner can control the auction object which he has legally and materially. And if there is a lawsuit, the winner of the auction should not participate as a defendant. This study discusses how the legal protection for the auction winner of the execution of mortgage over the control of the auction object and the obstacles experienced in the legal protection for the auction winner of the execution of the mortgage over the mastery of the auction object. The method used in this research is the normative juridical method, carried out through a literature study which examines mainly secondary data. The law has guaranteed legal certainty for auction buyers which is clearly stated in Vendu Reglement, HIR, and PMK Number 106/PMK.06/2013 concerning Amendments to PMK Number 93/PMK.06/2010 and PMK Number 93/PMK.06 /2010 Concerning Auction Implementation Guidelines. The Vendu Reglement is a regulation that regulates the basic principles of auction which has been in effect since April 1, 1908. In general, the Vendu Reglement only regulates the implementation of auctions, the auctioneer or currently referred to as the auction official, the parts and contents of the auction minutes. Article 42 of the Vendu Regulation states that the winner of the auction has the right to obtain a quote from the minutes of the auction as a deed of sale and purchase of the object of the auction. The excerpt of the minutes of the auction which will later be used as a deed of sale and purchase for the benefit of changing the name of the auction object if the object being auctioned is an immovable object. Keywords: Execution, Mortgage, Legal Protection, Auction Winner. AbstrakPerlindungan hukum terhadap pembeli lelang/pemenang lelang berarti adanya kepastian hukum hak pemenang lelang atas barang yang dibelinya melalui lelang, memperoleh barang dan hak kebendaan atas barang yang dibelinya atau dengan kata lain pemenang lelang dapat menguasai obyek lelang yang telah dimilikinya secara yuridis maupun secara materiil. Dan apabila terjadi gugatan, seharusnya pemenang lelang tidak turut serta sebagai tergugat. Penelitian ini membahas bagaimana perlindungan hukum bagi pemenang lelang eksekusi hak tanggungan atas penguasaan obyek lelang dan hambatan-hambatan yang dialami dalam perlindungan hukum bagi pemenang lelang eksekusi hak tanggungan atas penguasaan obyek lelang. Metode yang digunakan dalam penelitian ini yaitu Metode yuridis normatif dilakukan melalui studi pustaka yang menelaah terutama data sekunder. Undang-undang telah menjamin kepastian hukum bagi pembeli lelang yang secara jelas dinyatakan dalam Vendu Reglement, HIR, serta PMK Nomor 106/PMK.06/2013 Tentang Perubahan Atas PMK Nomor 93/PMK.06/2010 dan PMK Nomor 93/PMK.06/2010 Tentang Petunjuk Pelaksanaan Lelang. Vendu Reglement merupakan peraturan yang mengatur prinsip-prinsip pokok tentang lelang yang telah berlaku sejak 1 April 1908. Secara umum Vendu Reglement hanya mengatur tentang penyelenggaraan lelang, juru lelang atau saat ini disebut sebagai pejabat lelang, bagian-bagian serta isi dari risalah lelang. Dalam Pasal 42 Vendu Reglement, menyatakan bahwa pemenang lelang berhak memperoleh kutipan risalah lelang sebagai akta jual beli obyek lelang. Kutipan risalah lelang mana nantinya akan dipergunakan sebagai akta jual beli untuk kepentingan balik nama obyek lelang apabila yang dilelang adalah benda tidak bergerak.Kata kunci: Eksekusi, Hak Tanggungan, Perlindungan Hukum, Pemenang Lelang